Inclusion processes for persons with intellectual disability through multiple negotiation networks - Natascia Curto; Cecilia Maria Marchisio (Firenze University Press, 2022)
This article explores multiple aspects of the inclusion processes related to the CRPD (Convention on the Rights of persons with disabilities) implementation process carried out in Asti (NW Italy) between 2016 and 2020. For the purpose of this article, data have been collected regarding the work of social work professionals, who supported individuals and families following the methodology of "enabling co-design". The results show the necessity to allow interventions that create a support network to achieve full and equal citizenship, rethinking the transition to adult life through new epistemological categories that make it possible to overcome, both in theory and in practice, what is currently defined as a special adulthood. This goal may be achieved by adopting approaches that are more coherent with the scenario defined by the approval of the CRPD for the rights of persons with disabilities.   Processi di inclusione per persone con disabilità intellettiva attraverso le reti negoziali multiple. Questo articolo esplora molteplici aspetti dei processi di inclusione relativi al percorso di attuazione della CRPD svolto ad Asti tra il 2016 e il 2020. Ai fini del presente articolo sono stati raccolti dati relativi al lavoro degli operatori che hanno sostenuto persone con disabilità e famiglie seguendo l'approccio della coprogettazione capacitante. I risultati mostrano la necessità di promuovere interventi che creino una rete di supporto per raggiungere una cittadinanza piena e paritaria, ripensando il passaggio alla vita adulta attraverso nuove categorie epistemologiche che permettano di superare, sia in teoria che in pratica, ciò che è attualmente definito come un adulto speciale. Questo obiettivo può essere raggiunto adottando approcci più coerenti con lo scenario definito dall'approvazione della CRPD per i diritti delle persone con disabilità.